Contraception among adolescents in Bangladesh - M. Mazharul Islam; Mamun Mahmud (Asia-Pacific Population Journal, 1995)
The authors of this article are M. Mazharul Islam, Associate Professor, and Mamun Mahmud, research student, both in the Department of Statistics, University of Dhaka, Bangladesh.